2004
DOI: 10.1111/j.1440-1681.2004.04116.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lung Function With Atherosclerotic Risk Factors Among Japanese Americans: Seattle Nikkei Health Study

Abstract: 1. Impaired lung function has been reported to be associated with mortality from all causes, cardiovascular disease (CVD) and aortic pulse wave velocity (PWV). The aim of the present study was to examine the association between impaired lung function and atherosclerotic risk factors, including PWV, blood pressure, lipids, smoking and alcohol intake, among Japanese Americans. 2. The study subjects were 678 adult Japanese Americans who participated in CVD screening conducted under the Seattle Nikkei Health Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…Zureik and coworkers (84) found that PWV was associated with FEV 1 in 194 ostensibly healthy middle-aged men, independent of age, sex, and smoking status, although Taneda and colleagues (85) were unable to replicate this finding in 678 healthy Japanese Americans. Therefore, reduced pulmonary function may be associated with arterial stiffness in healthy individuals.…”
Section: Vascular Dysfunctionmentioning
confidence: 88%
“…Zureik and coworkers (84) found that PWV was associated with FEV 1 in 194 ostensibly healthy middle-aged men, independent of age, sex, and smoking status, although Taneda and colleagues (85) were unable to replicate this finding in 678 healthy Japanese Americans. Therefore, reduced pulmonary function may be associated with arterial stiffness in healthy individuals.…”
Section: Vascular Dysfunctionmentioning
confidence: 88%
“…First, low respiratory and cognitive functions are both aff ected by lifestyle behaviors such as smoking and drinking (31,32) as well as cardiovascular risk factors such as diabetes (33) and hypertension (34).…”
Section: Discussionmentioning
confidence: 99%
“…The Seattle Nikkei Health Study did not support the previously reported association of abnormal pulmonary function with aortic PWV. [28] Different clinical characteristics of participants may account for the differences in results from various reports. This study indicated for the first time that in CHF patients, CAVI was significantly correlated to FEV 1 after adjusting for confounders, supporting the notion of an association of pulmonary function with arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%